2009
DOI: 10.1021/jm9007278
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin−Cyclodextrin Conjugates as a Nanosystem for Versatile Drug Delivery and Multimodal Cancer Therapy

Abstract: The porphyrin-cyclodextrin conjugates were prepared and tested for selective and effective multifunctional drug delivery and therapy. The porphyrin receptor system combines efficient binding of the selected drug to the cyclodextrin cavity and photosensitizing properties of the porphyrin moiety with high accumulation of the whole complex in cancer tissue. The combined effect of chemotherapy and photodynamic therapy is demonstrated by in vitro and in vivo studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(37 citation statements)
references
References 44 publications
0
35
0
2
Order By: Relevance
“…They also conducted binding studies of several chemotherapy drugs with cyclodextrin (CD) for versatile drug delivery and in vitro and in vivo studies. 82 Binding studies revealed that doxorubicin has good binding affinity towards Por–γ-CD 3 and paclitaxel has good binding affinity towards Por–β-CD conju-gates 1, 2 and 4. Supramolecular carrier–chemotherapy drug complexes were then tested in vitro using 4T1 and human chronic myelogenous leukemia K562 cell lines, and in vivo using BALB/c mice transplanted with 4T1 cells.…”
Section: Substituted Fluorinated Porphyrinoids For Biological Applicamentioning
confidence: 98%
“…They also conducted binding studies of several chemotherapy drugs with cyclodextrin (CD) for versatile drug delivery and in vitro and in vivo studies. 82 Binding studies revealed that doxorubicin has good binding affinity towards Por–γ-CD 3 and paclitaxel has good binding affinity towards Por–β-CD conju-gates 1, 2 and 4. Supramolecular carrier–chemotherapy drug complexes were then tested in vitro using 4T1 and human chronic myelogenous leukemia K562 cell lines, and in vivo using BALB/c mice transplanted with 4T1 cells.…”
Section: Substituted Fluorinated Porphyrinoids For Biological Applicamentioning
confidence: 98%
“…This supramolecular nanoassembly simultaneously releases cytotoxic 1 O 2 and nitric oxide under illumination with visible light, resulting in amplified cancer-cell mortality [9]. By attaching porphyrin to γ-CD and dimeric β-CD, which are both able to form inclusion complexes with cytotoxic drug molecules such as doxorubicin and paclitaxel, nanocarriers with multimodal therapeutic effects (PDT and chemotherapy) have been developed by Král et al [1011]. The results achieved by these groups clearly demonstrated the numerous advantages of the PS–CD coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the same team synthesized a new Lego-like system composed of perfluorinated porphyrin–CD conjugates (P(CD) x ) and various chemotherapy drugs [ 140 ]. The perfluorinated porphyrins were first conjugated to CDs (β-CD or γ-CD) by covalent ether bond ( Figure 20 ) using the same strategy as described in their previous study [ 139 ].…”
Section: Cyclodextrins For Anticancer Photodynamic Therapymentioning
confidence: 99%